PENGARUH BAURAN PEMASAN TERHADAP KEPUTUSAN MEMBELI PRODUK OBAT HERBAL PAKUMAS DI KOTA BANJARMASIN - zulnedi, Zulnedi (JURNAL KINDAI, 2023)
Abstract: the study is aimed at analyzing the influence of promotions, prices, distribution and products on the decision to purchase the pakumas' herbal drug products in the flood city. 385 respondents get a sample taken, based on cochran formula (sugiyono, 2018:148). Research instruments through validity and religious tests and classic assumption tests involving normality, heterosity, multicolitarianism. Data analysis techniques using linear regression with the help of SPSS computer programs This research suggests, that: Promotion (x1), price (x2) distribution (x3) and product (x4) simultaneously significantly affected the decision to purchase (y) the pakumas herbal remedy product in the flood city Promotion (x1), price (x2), distribution and products (x4) in a partial way significantly affected the decision to purchase (y) the herbal products of mas nails in the city of banjarmasin. Product (x1) is dominant in importance to the mampurchase (y) needle herbal product in the flood city. This is proven with a beta variable product product of 0.479 greater than promotional, price and distribution variables. Keywords: promotion, price, distribution, product and decision to buy.